Buku dan Penyebaran Ideologi Radikal di Lembaga Pendidikan - Abu Rokhmad (International Journal Ihya' 'Ulum al-Din, 2018)
This article aims to examine the use of religious reading books as a medium for the dissemination of radical ideologies in educational institutions. The role of the book as a window of knowledge is undoubted, but the book as a disseminator of radicalism also gets justification. Hardline Islamic groups have used certain reading books as justifiers and reinforcement of the radical notions believed. The contents of the book are then taught and indoctrinated to students and students by teachers through a single interpretation and normative-scriptural approach